Life cycle assessment for solid waste disposal options in Malaysia - Saheri, S.; Mir, M.A.; Basri, N.E.A.; Mahmood, N.Z.; Begum, R.A. (2012)
The largest percentage of MSW in Malaysia is contributed by the state of Selangor, with a 3,923 tons generated daily. Therefore, the aim of this study is to consider the current condition of the open dumps and sanitary landfills in Selangor from an environmental point of view. Moreover, the local authorities of Malaysia prefer to use landfills that have no liners, biogas capture, and many others as a method of getting rid of collected waste. In Malaysia, this is the first time life cycle assessment (LCA) is being used. In this study, LCA is used to weigh up different treatment scenarios and SimaPro7 (2006) software with CML 2 base line 2000 v2.04 methodology applied to model the three scenarios. Research has shown that all scenarios have a high amount of different potential impacts. Further analysis illustrated that S3 (100 sanitary landfill) is more preferable than the others because of its low contribution on eutrophication, global warming and photochemical oxidation impacts. Results also confirmed that landfilling, which is the current waste disposal method for the country, is not a preferable method environmentally. Further studies should involve other decision-making tools and a wide range of scenarios that consider the economic and social effects of solid waste management methods to introduce environmentally and economically preferable methods to the Malaysian authorities.